Progress in Treatment of Temporomandibular Joint Disorder - Wei YANG; Minghua XIE; Yu CAI; Zhuoming CHEN (康复学报)
We review the researchs of temporomandibular joint disorder (TMD) in domestic and foreign scholars, respectively, to explain in four aspects, such as etiology, clinical characteristics, treatment methods and preventive measures. TMD ranks fourth in oral epidemiology, which is related to estrogen levels in patients, female prevalence is higher than male, high prevalence among young adults. The temporomandibular joint alignment, local muscle stability, low immunity, repeated chewing of hard and large food, and long-term unilateral chewing, etc., will lead to the onset or aggravation. TMD is divided into functional disorder, structural disorder, and joint organic destruction, and with a gradual development trend. The clinical manifestations are pain in the joint area or master muscle. There are joints or murmurs during joint opening, joint movement posture, rang of motion (ROM), opening type and other abnormalities. In stomatology department, including occlusal plywood training, denture repair, orthodontic, adjustment, crown and bridge repair, occlusal reconstruction and other means are used to relieve the pain; traditional Chinese medicine carries on the syndrome differentiation treatment of internal administration and external application, combined with acupuncture, floating needle, fire needle, warm acupuncture, thunder fire moxibustion, heat sensitive moxibustion, filiform needle, acupoint injection, medicine separated moxibustion, etc., the curative effect is remarkable; He-Ne laser therapy could activate the intracranial morphine peptide system, inhibit the release of pain causing substances; when the conservative treatment is ineffective, minimally invasive surgery under the arthroscope can be selected to release adhesion and improve spasm. There are many physical factor therapy methods, including low, medium and high frequency electrotheraphy, manipulation, mandibular joint training, local ultrasonic therapy, muscle energy technology and so on; manipulation treatment includes western massage and Chinese chiropractic manipulation reduction; non-painkiller and muscle relaxant are commonly used in western medicine in order to reduce muscle spasm and relieve pain. Cognitive behavioral therapy (CBT) will correct negative factors such as psychogenic sleep disorder, anxiety, depression and so on. Medical-biological-psychological model, perfects the three-level prevention mechanism of etiology, disease and disability, and suppresses the occurrence of TMD from the source, which is provided for prevention with the help of healthy lifestyle. The treatment methods at present have certain clinical curative effects. It is suggested that a multidisciplinary and multimodal study be conducted on the efficacy of the treatment for the limitations of their respective specialties, and the scope of diagnosis and treatment and the diagnosis and treatment process of each department should be standardized step by step.